Calculation and internal validation of a new synthetic and autocorrelate index to combine the determinants of health of a population - Domenico Tebala; Giovanni Domenico Tebala (BMC, 2021)
Abstract Background The status of health of an individual and - more broadly - of a community or population is defined by the status of their determinants of health. A "systemic" approach to define the health determinants is necessary in order to explore the complex relations existing among them. This study is aimed at identifying a 'composite systemic' index of health to measure the impact of socioeconomic factors on public health at local level and to analyze possible spatial autocorrelations between neighboring regions. Results A Composite Index of Health (CIH) was constructed on the basis of known indicators of socio-economic well-being by using the COMIC (COMposite Indices Creator) Software and was validated on the Italian population and a nationwide comparison has been performed. Analysis of the determinants showed a significant direct correlation between health, environment, work and wealth and inverse correlation between health and social distress. The analysis of data from Italian provinces confirmed the South-North gradient of well-being. Conclusion The CIH is a reliable and robust index to evaluate the health of a local population. Although it was validated on Italian data, the index can be easily adapted to any Country.